Introduction to multicopter design and control - Quan, Quan (Springer, 2017)
This book is the first textbook specially on multicopter systems in the world. It provides a comprehensive overview of multicopter systems, rather than focusing on a single method or technique. The fifteen chapters are divided into five parts, covering the topics of multicopter design, modeling, state estimation, control, and decision-making. It differs from other books in the field in three major respects: it is basic and practical, offering self-contained content and presenting hands-on methods; it is comprehensive and systematic; and it is timely. It is also closely related to the autopilot that users often employ today and provides insights into the code employed. As such, it offers a valuable resource for anyone interested in multicopters, including students, teachers, researchers, and engineers.
Keywords: Helicopters -- Models -- Design.; Helicopters -- Models -- Radio control.; elektronické knihy; electronic books